Complete Blood Count as point of care testing QBC STAR™: Preliminary evaluation. (22nd March 2021) - Napolitano, Gavino; Caracciolo, Alessandra; Apassiti Esposito, Sara; Della Malva, Nunzia; Manenti, Barbara; Guerra, Giovanni; Ottomano, Cosimo; Lippi, Giuseppe; Buoro, Sabrina
Abstract: Introduction: Point of care testing (POCT) represents a valuable option when laboratory data shall be urgently available for timely clinical management, with a turnaround time (TAT) that is unfeasible using conventional laboratory instrumentation. This study was aimed to compare the performance of QBC STAR™ compared to Sysmex XN‐module and the reference optical microscopy (OM) assessment. Material and Methods: One hundred peripheral blood samples, collected in K3 EDTA tubes, and 50 capillary blood samples obtained by finger stick were analyzed with QBC STAR™, Sysmex XN‐module, and OM. Data were compared with Passing‐Bablok regression and Bland‐Altman plots. Results: The Passing‐Bablok regression analysis (QBC STAR™ capillary sample vs XN‐module) yielded slopes comprised between 0.30 and 1.37, while the intercepts ranged between −17.57 and 232.6. Bland‐Altman plots yielded relative bias comprised between −4.87% (for MN QBC STAR™ capillary sample vs XN‐module) and 27% (PLT QBC STAR™ capillary sample vs XN‐module). A significant bias was found for all parameters except MN and WBC, RBC in all and pediatric samples, and HB in adults samples. Conclusion: The results of this analytical evaluation suggest that QBC STAR™ may not be the ideal tool for performing complete blood count analysis for diagnostic purposes, while it could be more useful in urgent/emergent conditions, such as for rapid monitoring of some hematological parameters (eg, WBC and HB).